2006
DOI: 10.1016/j.ssc.2006.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Polaronic effects in asymmetric quantum wire: An all-coupling variational approach

Abstract: An all-coupling variational calculation based on Lee-Low-Pines-Huybrechts (LLPH) theory is performed to study the ground state and the first excited state in an asymmetric polar semiconductor quantum wire that is valid for the entire range of the electron-phonon coupling constant and arbitrary confinement length. It is shown that the polaronic effects are very important and size dependent, if the effective width of the wire is reduced below a certain length scale. It is also shown that asymmetry in a quantum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…[17,[21][22][23][24][25][26][27][28]). Degani and Hipólito [21] have calculated the polaron self-energy (PSE) and the effective mass (PEM) in the GaAs/GaAlAs QWR using a variational approach which is based on the canonical transformation method of Lee, Low and Pines (LLP) [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,[21][22][23][24][25][26][27][28]). Degani and Hipólito [21] have calculated the polaron self-energy (PSE) and the effective mass (PEM) in the GaAs/GaAlAs QWR using a variational approach which is based on the canonical transformation method of Lee, Low and Pines (LLP) [29].…”
Section: Introductionmentioning
confidence: 99%
“…Xie [26] has considered a freestanding cylindrical QWR and obtained the PSE and correction to the electron effective mass due to electron-LO-phonon interaction and also electron-surface optical phonon interaction using the second-order perturbation theory and taking into account the contributions from higher energy subbands. Within the framework of Lee-Low-Pines-Huybrechts variational theory Krishna et al [27,28] have investigated the polaronic binding energies corresponding to the ground state and the first excited state of an electron in a polar quantum wire with parabolic confinement in the transverse direction and it has been shown that even the longitudinal PEM is strongly enhanced by the transverse confinement in a QWR. Recently, the ground state PSE and PEM due to the quasi-confined and surface optical phonon modes in a freestanding wurtzite GaN NW are studied by employing the second-order perturbation approach [17,30] and LLP variational approach [31].…”
Section: Introductionmentioning
confidence: 99%
“…In the frame of the Rayleigh-Schrödinger perturbation theory, the polaron problem is discussed in a QWR made of a wurtzite-type material [7]. An all-coupling variational calculation based on the Lee-Low-Pines-Huybrechts theory is performed to study the polaron ground state and the first excited state in an asymmetric polar semiconductor QWR [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering experimental work of Fan's group 1 on the synthesis of the first wurtzite GaN nanorods, the quasi‐1‐dimensional (Q1D) GaN‐based nanowires (NWs) have attracted a considerable amount of attentions both in theoretical and experimental investigations 1–16. This is mainly due to the following three evident facts: the nitride materials (including GaN, AlN, InN, and their ternary compounds, AlGaN and InGaN) with strong atomic bonding and wide and adjustable direct‐bandgap, which make them quite potential as a basis for the creation of reliable high‐temperature and high‐frequency nano‐optoelectronic devices such as field‐effect‐transistors (FETs), high‐brightness blue/green light‐emitting diodes and laser diodes as well as photodetectors 2–5; Q1D structure' confinement of NWs for carriers in two dimensions and freedom in the last dimension, promising more efficient lasers and optical gain as well as possible applications for optical waveguide and photovoltaic elements in comparisons with quantum wells (QWs) and quantum dots (QDs) 6–10; the Q1D NW systems also playing an important role in testing and understanding fundamental concepts, such as the role of dimensionality and size in optical, electrical, and mechanical properties 11–16. Hence the investigation of electronic and optoelectronic properties in GaN‐based NWs has become a hot topic during the last decade for their concomitant advantages of possessing both excellent optoelectronic properties and nanoscale dimensions.…”
Section: Introductionmentioning
confidence: 99%